BLENDED LEARNING DENGAN MACROMEDIA FLASH UNTUK MELATIH KEMANDIRIAN BELAJAR MAHASISWA - Octaria, Dina; Fitriasari, Putri; Sari, Novita (Jurnal Elemen, 2020)
Learning independence among students is still low. It can be seen from the students being less active in finding learning resources and only waiting from the lecturers, from the task of making learning media given by students there are still many who only copy and edit it. To practice learning independence, innovation is needed in learning, one of which uses learning that combines face-to-face and virtual learning, namely blended learning. This study aims to train the independence of student learning in making learning media based on Macromedia flash through blended learning. The research method used is quantitative descriptive method. The sample in this study were 28 students of the mathematics education program at the PGRI University of Palembang. The research instrument was a student learning independence questionnaire given before and after learning. The quantitative data obtained were analyzed descriptively. The results showed that student learning independence changes before and after learning, with the largest percentage change in the indicators of self-efficacy (self-concept), while the smallest percentage of changes in the indicators evaluating the learning process and results. Besides, the efforts that can be made to train the independence of student learning with blended learning are providing a discussion forum; giving assignments to each material so that students know clearly the learning objectives; conducting discussions on each assignment given, and; do not limit students in access learning resources.